A review of walking energy harvesting using piezoelectric materials - Nia, E.M. (Institute of Physics Publishing, 2018)
Harvesting kinetic energies is a sustainable method for generating electricity without depleting natural resources. The main mechanisms for kinetic energy harvesting are piezoelectric, electromagnetic, electrostatic or by using magnetostrictive materials. This study focuses on harvesting of walking energy and aims to compare different technologies used for converting of walking energy to electricity, and identify the most effective technology. Several types of harvester located on body of user to harvest kinetic energy of body during walking, while some pavement slabs are produced for harvesting energy. The paper concludes that the pavement equipped with the harvesters would be more reliable than the body located technologies since it is independent of the physiological parameters. Moreover, the piezoelectric transduction is more desirable due to its advantages such as simplicity and flexibility, while produce less current output than the electromagnetic transduction. Â© Published under licence by IOP Publishing Ltd.